Enforcement of Law on Environmental Violations by Mining Companies in Indonesia - Sedarto, Teguh; Kagramanto, Lucianus Budi; Anggriawan, Teddy Prima; Albany, Rasha Firmana (Future Science, 2023)
This journal scrutinizes the legal enforcement concerning environmental violations committed by mining companies in Indonesia. The study explores the practical implementation and effectiveness of legal measures in shielding the environment from the adverse impacts associated with mining activities. Through an analysis of regulatory frameworks and case studies, the research evaluates the challenges and successes in enforcing environmental laws within the mining sector. Findings indicate the complexity of regulations and challenges faced in on-the-ground enforcement. Nevertheless, notable successes are also recorded in mitigating negative environmental impacts. The research contributes to our understanding of law enforcement efforts and policy expansion to address environmental challenges. It highlights the importance of robust legal mechanisms in reducing the environmental footprint of mining operations in Indonesia. The study has the potential to guide policy improvements and more sustainable practices in engaging mining companies while maintaining a balance between economic growth and environmental sustainability. The intricacies uncovered in this research offer insights into the dynamics of environmental law enforcement and suggest avenues for refining regulatory frameworks to better address the evolving landscape of environmental concerns in the context of mining activities in Indonesia.